Environment, diversity and family: Franco’s education from the voices of its students - Monforte-García, Estefanía; Jiménez-Andújar, Eva María; Alcalá Ibáñez, Mª Lourdes (Revista Complutense de Educación, 2024)
The oral testimonies of students from the Franco era presented here offer a unique perspective on elements that have been little studied in the various works published on the subject. The aim of this study is to analyse the education of the Franco regime through the oral testimonies of its protagonists and to offer a vision of original elements such as the relationship with the environment and learning for life, the treatment of diversity and accessibility and the family-school relationship. The information was collected through 94 interviews with men and women aged between 45 and 90 years old and carried out by students in the first year of the Degree in Primary Education at the University of Zaragoza. The results obtained reveal that the school contents were perceived as decontextualised and difficult to transfer to their daily lives, except for those related to sex. Also, the partial or total exclusion of pupils with special educational support needs and the scarce family-school relationship and communication, mainly during the first Franco regime, are evidenced.